Cross sex hormone treatment is linked with a reversal of cerebral patterns associated with gender dysphoria to the baseline of cisgender controls. (21st May 2019) - Kilpatrick, Lisa A.; Holmberg, Mats; Manzouri, Amirhosein; Savic, Ivanka
Abstract: Transgender persons experience incongruence between their gender identity and birth‐assigned sex. The resulting gender dysphoria (GD), is frequently treated with cross‐sex hormones. However, very little is known about how this treatment affects the brain of individuals with GD, nor do we know the neurobiology of GD. We recently suggested that disconnection of fronto‐parietal networks involved in own‐body self‐referential processing could be a plausible mechanism, and that the anatomical correlate could be a thickening of the mesial prefrontal and precuneus cortex, which is unrelated to sex. Here, we investigate how cross‐sex hormone treatment affects cerebral tissue in persons with GD, and how potential changes are related to self‐body perception. Longitudinal MRI measurements of cortical thickness (Cth) were carried out in 40 transgender men (TrM), 24 transgender women (TrW) and 19 controls. Cth increased in the mesial temporal and insular cortices with testosterone treatment in TrM, whereas anti‐androgen and oestrogen treatment in TrW caused widespread cortical thinning. However, after correction for treatment‐related changes in total grey and white matter volumes (increase with testosterone; decrease with anti‐androgen and oestrogen), significant Cth decreases were observed in the mesial prefrontal and parietal cortices, in both TrM and TrW (vs. controls) – regions showing greater pre‐treatment Cth than in controls. The own body – self congruence ratings increased with treatment, and correlated with a left parietal cortical thinning. These data confirm our hypothesis that GD may be associated with specific anatomical features in own‐body/self‐processing circuits that reverse to the pattern of cisgender controls after cross‐sex hormone treatment. Abstract : This MR study of corticial thickness (Cth) investigates effects of cross sex hormone treatment in transgender men (TrM) and transgender women (TrW). While 'feminizing' treatment with antiandrogens and estradiol in TrW leads to widespread cortical thinning, testosterone treatment in TrM causes an increased thickness of the insular and mesial temporal cortex. However, when correcting for global estrogen and testosterone associated changes in the total white matter and grey matter volume, both transgender groups showed a relative tinning of the mesial frontal cortex and parietal cortex, regions in which we before treatment detected increased Cth. Thus, cross sex hormone treatment seems to be linked with a reversal of cerebral patters associated with gender dysphoria to the baseline of cisgender controls.